Understanding the Role of the Master Regulator XYR1 in Trichoderma reesei by Global Transcriptional Analysis - dos Santos Castro, Lilian; de Paula, Renato G.; Antoniêto, Amanda C. C.; Persinoti, Gabriela F.; Silva-Rocha, Rafael; Silva, Roberto N. (Frontiers in Microbiology, 2016)
We defined the role of the transcriptional factor–XYR1–in the filamentous fungus Trichoderma reesei during cellulosic material degradation. In this regard, we performed a global transcriptome analysis using RNA-Seq of the ∆xyr1 mutant strain of T. reesei compared with the parental strain QM9414 grown in the presence of cellulose, sophorose, and glucose as sole carbon sources. We found that 5885 genes were expressed differentially under the three tested carbon sources. Of these, 322 genes were upregulated in the presence of cellulose, while 367 and 188 were upregulated in sophorose and glucose, respectively. With respect to genes under the direct regulation of XYR1, 30 and 33 are exclusive to cellulose and sophorose, respectively. The most modulated genes in the ∆xyr1 belong to Carbohydrate-Active Enzymes (CAZymes), transcription factors, and transporters families. Moreover, we highlight the downregulation of transporters belonging to the MFS and ABC transporter families. Of these, MFS members were mostly downregulated in the presence of cellulose. In sophorose and glucose, the expression of these transporters was mainly upregulated. Our results revealed that MFS and ABC transporters could be new players in cellulose degradation and their role was shown to be carbon source-dependent. Our findings contribute to a better understanding of the regulatory mechanisms of XYR1 to control cellulase gene expression in T. reesei in the presence of cellulosic material, thereby potentially enhancing its application in several biotechnology fields.